Inequality, redistribution and mobility - Rodriguez, Juan Gabriel; Bishop, John A. (Research on Economic Inequality Ser., 2020)
Research on Economic Inequality's 28th volume provides original research on how inequality is affected by redistribution, growth, mobility and educational opportunities. Additional papers discuss poverty, welfare and wage discrimination.